Integrated Farming Systems Approach for Income Enhancement and Employment Generation in North-West India - Ravinder Singh and T. S. Riar, (Indian Journal of Extension Education, 2014)
Astudy was conducted during 2011-12 in Punjab to find out the productivity, profitability and employment generation ofintegrated farming system as compared to conventional cropping system. The study comprised of two integrated farmingsystems viz., crop + floriculture and crop + bee-keeping. Both these integrated farming systems were productive andprofitable than that of sole cropping system. The net returns increased in the tune of 29.53 per cent and 19.09 per cent perhectare with inclusion of floriculture and bee-keeping enterprises, respectively over sole cropping system. The study alsoindicated that crop + floriculture farming system generated 31.03 mandays/hectare/annum/farm employment for family,46.14 mandays/hectare/annum/farm for hired labour and 77.17 mandays/hectare/annum/farm as total labour. In case ofcrop + bee-keeping, it was observed that employment generated through crop + bee-keeping farming system for familylabour was 29.61 mandays/hectare/annum/farm, for hired labour was 40.12 mandays/hectare/annum/farm and for totallabour was 69.73 mandays/hectare/annum/farm.